2020
DOI: 10.1186/s12895-020-00099-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of psoriasis in hard-to-treat body locations: data from the Danish skin cohort

Abstract: Background: Having psoriasis in hard-to-treat areas, i.e. the scalp, face, palms, soles, nails, and genitals, respectively, can impair patients' quality of life. We investigated the prevalence of hard-to-treat body locations of psoriasis, and described patients' clinical and demographic characteristics, and quality of life impacts in a population-based cohort. Methods: We performed a cross-sectional study using a total of 4016 adults (≥18 years) with psoriasis from the Danish Skin Cohort. Groups were compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
44
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 36 publications
10
44
1
2
Order By: Relevance
“…This can be illustrated for specific body sites, such intertriginous skin, scalp, or nails, to provide important clinical insights into differential treatment responses to targeted psoriatic therapies. Many clinical trials and real-world studies have previously shown that special sites of skin (e.g., scalp, nails, joints, palms/soles) do not always respond in line with the observed skin response [ 18 , 19 ]. Varied individual response could be related to treatment compliance, natural fluctuations in a patient’s immune response, and/or external triggers of disease, such as trauma, infections, scratching and stress.…”
Section: Discussionmentioning
confidence: 99%
“…This can be illustrated for specific body sites, such intertriginous skin, scalp, or nails, to provide important clinical insights into differential treatment responses to targeted psoriatic therapies. Many clinical trials and real-world studies have previously shown that special sites of skin (e.g., scalp, nails, joints, palms/soles) do not always respond in line with the observed skin response [ 18 , 19 ]. Varied individual response could be related to treatment compliance, natural fluctuations in a patient’s immune response, and/or external triggers of disease, such as trauma, infections, scratching and stress.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review shows that men and women are equally affected by nail psoriasis, and its prevalence increases with the age of the study population [26]. Results from a Danish skin cohort with a total of 4016 adults with psoriasis showed that the most frequently affected hard-to-treat area was the scalp (43.0%), followed by the face (29.9%), nails (24.5%), soles (15.6%), genitals (14.1%), and palms (13.7%) [27]. Similarly to our study results, higher prevalence was generally seen with increasing psoriasis severity and patients with involvement of certain hard-totreat areas such as hands, feet, and genitals had clinically relevant DLQI impairments.…”
Section: Discussionmentioning
confidence: 99%
“…Nail involvement on fingers and/or toes is frequent in psoriasis, with 25% [1] to 41% [2] of patients affected. It is also a marker of increased disease severity of psoriasis and psoriasis arthritis [3][4][5].…”
Section: Quality Of Life In People With Nail Psoriasismentioning
confidence: 99%